The (my)Grid ontology: bioinformatics service discovery - Wolstencroft, K; Alper, P; Hull, D; Wroe, C; Lord, P W; Stevens, R D; Goble, C A (International journal of bioinformatics research and applications, 2007)
(my)Grid supports in silico experiments in the life sciences, enabling the design and enactment of workflows as well as providing components to assist service discovery, data and metadata management. The (my)Grid ontology is one component in a larger semantic discovery framework for the identification of the highly distributed and heterogeneous bioinformatics services in the public domain. From an initial model of formal OWL-DL semantics throughout, we now adopt a spectrum of expressivity and reasoning for different tasks in service annotation and discovery. Here, we discuss the development and use of the (my)Grid ontology and our experiences in semantic service discovery.